Employee Turnover Intention in Manufacturing: The Role of Transformational Leadership and Work Stress at XYZ Company - Khitara Aldilla Chandra; Muhammad Tegar Irsyadi; Deti Kirana (DPPM Universitas Pelita Bangsa, 2026)
Employee turnover intention is a retention risk in manufacturing because it can disrupt production continuity, reduce efficiency, and increase replacement costs. This study examines how work stress and transformational leadership predict employee turnover intention at XYZ Company in Bekasi. The study used a quantitative causal design with saturated sampling. Data were collected offline in 2026 through structured questionnaires distributed to all 86 employees from production, warehouse, quality control, administration, and customer service divisions. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS to assess the measurement and structural models simultaneously. The results show that work stress has a positive and significant effect on employee turnover intention and is the slightly stronger predictor. Transformational leadership has a negative and significant effect, indicating that supportive leadership can reduce employees’ intention to leave. The model explains 63.5 percent of the variance in turnover intention. This study contributes to human resource management literature by positioning work stress as a job demand and transformational leadership as a job resource in explaining retention risk within an Indonesian manufacturing context. The findings suggest that companies should prioritize stress management while strengthening transformational leadership at supervisor and unit-head levels.